RUST OF PERENNIAL ONIONS - K. L. Alekseeva; M. I. Ivanova; A. I. Kashleva (Овощи России, 2016)
Significant damage to cultivated perennial onions is caused by rust disease (Puccinia allii (DS.) Rud.). The 15 types of perennial onions (17 cultivars and 13 breeding specimens) were tested for resistance to diseases in the conditions of Moscow region. The high degree of susceptibility to rust disease is common to Allium nutans (= Siberian chives or blue chives), Allium schoenoprasum (=chives), Allium galanthum (= snowdrop onion) and Allium amphibolum (the degree of the disease development was more than 15%). Among the varieties of welsh onions the highest degree of resistance to disease was common to the early ripening variety Sprinter. The Allium odorum (= garlic chives), Allium obliquum and Allium senйscens (= German garlic or broadleaf chives) were not susceptible to rust infection. The article discusses the ways of onion protection from rust disease.